Anthocyanin and Organoleptic Analysis of Red Bean Flour Steamed Sponge Cake with the Addition of Butterfly Pea Flower Extract (Clitoria ternatea Linn.) - Rizki Febrianti; Ninna Rohmawati; Septy Handayani (Window of Health : Jurnal Kesehatan, 2025)
Butterfly pea flower is a plant that is commonly found by the public in abundant quantities, which contains anthocyanins, so it is useful for improving human health, acting as an antioxidant, anti-diabetic, anti-obesity, anti-inflammatory, anti-cancer, anti-allergic, anti-arthritis, and anti-hyperglycemic, and treats various diseases, one of which is diabetes mellitus. Type 2 diabetes mellitus predominantly occurs due to lifestyle, so it is susceptible to the whole community and is predicted to increase by 2030. This research aims to determine the anthocyanin and organoleptic levels of steamed red bean flour cake with the addition of butterfly pea flower extract. Measurement of anthocyanin levels uses the AOAC Official method 2002.02 analysis method, and for organoleptic testing uses the hedonic scale test form. Anthocyanin levels increased with the addition of butterfly pea flower extract. Anthocyanin levels experienced a significant increase. The results of organoleptic tests on steamed red bean flour sponge cake with the addition of butterfly pea flower extract showed that the aroma, taste, and texture were not different, while the color was different. The best formulation based on the MPE method is X3 with a recommended consumption of 1 piece or 50 grams.